Photoactive TiO2 Films Formation by Drain Coating for Endosulfan Degradation - Natalia Tapia-Orozco; Refugio Rodríguez Vázquez (International Journal of Photoenergy)
Heterogeneous photocatalysis is an advanced oxidation process in which a photoactive catalyst, such as TiO2, is attached to a support to produce free radical species known as reactive oxygen species (ROS) that can be used to break down toxic organic compounds. In this study, the draining time, annealing temperature, and draining/annealing cycles for TiO2 films grown by the drain coating method were evaluated using a 23 factorial experimental design to determine the photoactivity of the films via endosulfan degradation. The TiO2 films prepared with a large number of draining/annealing cycles at high temperatures enhanced (P>0.05) endosulfan degradation and superoxide radical generation after 30 minutes of illumination with UV light. We demonstrated a negative correlation (R2=0.69; P>0.01) between endosulfan degradation and superoxide radical generation. The endosulfan degradation rates were the highest at 30 minutes with the F6 film. In addition, films prepared using conditions F1, F4, and F8 underwent an adsorption/desorption process. The kinetic reaction constants, Kapp (min−1), were 0.0101, 0.0080, 0.0055, 0.0048, and 0.0035 for F6, F2, F5, F3, and F1, respectively. The endosulfan metabolites alcohol, ether, and lactone were detected and quantified at varying levels in all photocatalytic assays.